A STUDY OF THE VALUE AT RISK OF TOP 5 COMPANIES IN INDIA DURING COVID ERA - Dr. Abhishek Tripathi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
On 24 March 2020, the Government of India requested a cross country lockdown for 21 days, restricting development of the whole 1.3 billion populace of India as a preventive measure against the COVID-19 pandemic in India. It was requested following a 14-hour willful public check in time on 22 March, trailed by implementation of a progression of guidelines in the nation's COVID-19 influenced districts.